Effect of obstructive jaundice on hepatic hemodynamics: use of Sonazoid-enhanced ultrasonography in a prospective study of the blood flow balance between the hepatic portal vein and hepatic artery - Wakui, Noritaka; Takeda, Yuki; Nishinakagawa, Shuta; Ueki, Nobuo; Otsuka, Takafumi; Oba, Nobuyuki; Hashimoto, Hiroshi; Kamiyama, Naohisa; Sumino, Yasukiyo; Kojima, Tatsuya (Journal of Medical Ultrasonics, 2015)
Purpose To prospectively clarify the effects of obstructive jaundice (OJ) on hepatic hemodynamics using contrast-enhanced ultrasonography (US). Methods Subjects comprised 14 patients admitted to our hospital for OJ between April 2013 and March 2014. Contrast-enhanced US was performed using the LOGIQ E9 ultrasound device during the jaundice phase, before biliary drainage, and again after improvement of jaundice. After injecting the Sonazoid contrast agent, contrast dynamics were recorded in the right kidney and liver segments 5 or 6. Prototype software was used to calculate mean arrival time (AT) of the contrast agent in the liver parenchyma. Statistical analysis was performed to compare the mean AT in the jaundice and improved jaundice phases. Results We were unable to follow up three of the 14 patients after biliary drainage; thus, we included 11 patients for further analysis. The mean AT of the contrast agent was 2.0 ± 1.8 and 6.1 ± 2.3 s in the jaundice and improved jaundice phases, respectively, showing significantly shorter AT in the jaundice phase ( p = 0.0033). Conclusion Our findings indicate that OJ may influence the blood flow balance between the hepatic portal vein and hepatic artery.